Manipulation of Proteins on Mica by Atomic Force Microscopy - Lea, A. S. (1992)
The atomic force microscope was used to image adsorption of a monoclonal IgM on mica in real time. Under the smallest possible force we could achieve (<4 nN), the cantilever tip behaved as a molecular broom and was observed to orient protein aggregates in strands oriented perpendicularly to the facet of the cantilever tip. Rotating the scan direction preserved the orientational relationship, as seen by the formation of rotated strands. When the applied force was increased, the distance between the strands increased, indicating the amount of protein that can be swept depends on the applied force. The effect of scanning increased the apparent surface coverage of IgM. Manipulation of a deposited fibrinogen layer with a 4-nN repulsive force was observed only after tens of minutes, but not to the extent that strands formed, indicating a greater adhesion between the fibrinogen and mica than between IgM and mica. With an applied repulsive force of 30 nN, fibrinogen strands formed and the protein was manipulated to produce the block letter U. At a much higher repulsive force, the entire scanning area was swept clean.